A paz pelo caminho da lei: Juan Bautista Alberdi e o pensamento político hispano-americano do século XIX - Silva, Tito Souza da (2014)
It studies the political thought of Juan Bautista Alberdi (1810-1884), one of the main intellectuals of the Hispanic America, member of the so called Generation 37. It outstands the following aspects of that generation's writings: the arguments that comprised the so called 'genetic concept of nation', the importance of the christian religion, and the criticism to Juan Manuel de Rosas's government. It analyzes the work ‘Bases’, highlighting the following principles: the importance of immigration for the education of the masses, the civil freedom for the country's industrial and commercial development, the limited political freedom, and the need of a strong executive. It refutes the interpretation that understands the Hispanic-American thought as a 'detour' from the European liberalism, establishing a parallel between Alberdi's thought with the European liberals', such as Montesquieu and Adam Smith. Then, it analyzes the work El crimen de la guerra, where Alberdi proposes the creation of a povo-mundo up from the trade and from the moral principles of christianity. It highlights the christian religion’s presence in the classical liberalism, in order to demonstrate that it is not a specific element of Alberdi's thought.